2009
DOI: 10.1016/j.peptides.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new bioactive peptide from Potamotrygon gr. orbignyi freshwater stingray venom

Abstract: Brazilian freshwater stingrays, Potamotrygon gr. orbigyni, are relatively common in the middle-western regions of Brazil, where they are considered an important public health threat. In order to identify some of their naturally occurring toxin peptides available in very low amounts, we combine analytical protocols such as reversed-phase high-performance liquid chromatography (RP-HPLC), followed by a biological microcirculatory screening and mass spectrometry analysis. Using this approach, one bioactive peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
0
24
1
5
Order By: Relevance
“…henlei collected in Tocantins, together with a general biochemical and biological characterization of the samples of venom and mucus studied are reported. To the best of our knowledge, there is only a couple of reports dealing with the experimental toxicity of Potamotrygon stingray venoms [14] and [17], the characterization of two peptides [29,30] and the presence of a protein with hyaluronidase activity [42]. The venom of P. cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…henlei collected in Tocantins, together with a general biochemical and biological characterization of the samples of venom and mucus studied are reported. To the best of our knowledge, there is only a couple of reports dealing with the experimental toxicity of Potamotrygon stingray venoms [14] and [17], the characterization of two peptides [29,30] and the presence of a protein with hyaluronidase activity [42]. The venom of P. cf.…”
Section: Discussionmentioning
confidence: 99%
“…This work leads us to a better and more detailed study of this venom and its compounds, purifying toxins to allow pharmacological investigations. By this approach, we isolated two bioactive peptides from the venom of the P. gr orbignyi freshwater stingray [29,30]. These peptides, called orpotrin and porflan, shown to be effective in the microcirculatory environment, induce strong vasoconstriction and inflammation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, vasoconstrictor and microcirculatory active peptide were isolated from Potomotrygon gr. orbignyi venom [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Screening of antibacterial drugs from marine gastropod Chicoreus ramosus has also been done most recently by Ramasamy et al [20] . Stingray venom is a potential source of novel bioactive peptide like Orpotrin and Porflan [21] . Prabhu et al (2013) demonstrated the crude and fractions of starfish Stellaster equestris have remarkable antimicrobial activities against human bacterial pathogens [22] .…”
Section: Discussionmentioning
confidence: 99%